CRISPR-Cas Loci of Yersinia pseudotuberculosis Strains with Different Genetic Determinants - N. P. Peretolchina; V. T. Klimov; E. A. Voskresenskaya; G. I. Kokorina; E. A. Bogumilchik; A. L. Trukhachev; S. V. Igumnova; Y. P. Dzhioev; V. I. Zlobin (Эпидемиология и вакцинопрофилактика)
Relevance. Yersinia pseudotuberculosis is a causative agent of pseudotuberculosis, a disease with polymorphism of clinical manifestation that is determined by the presence of specific virulence determinants: plasmid pVM82, pathogenicity islands HPI and YAPI, and superantigen YPM. Occurrence of new determinants depends on horizontal transfer of mobile genetic elements, hence, systems regulating horizontal transfer participate in evolution of pathogenic species. CRISPR-Cas is and adaptive protection system of prokaryotes against mobile genetic elements. Aim. The study analyzed an interaction between CRISPR-loci of Y. pseudotuberculosis and virulence determinants. Results. 86% of strains includes three CRISPR-loci: YP1, YP2, and YP3. Length of locus YP3 mostly depends on presence of virulence determinants in strains of Y. pseudotuberculosis serotype O:1b. Strains with virulence genes are able to cause a severe form of pseudotuberculosis and have longer locus than strains without determinants. Conclusion. Therefore, CRIPSRCas system of Y. pseudotuberculosis may participate in formation of a certain strain genotype that defines clinical manifestation of pseudotuberculosis.